Lifetime physical fitness and wellness a personalised program - Hoeger, Werner W. K.; Hoeger, Sharon A.; Hoeger, Cherie I.; Fawson, Amber L. (Cengage Learning, 2019)
Assess your current behaviors, identify potential problem areas and apply practical steps to start positive changes. Vivid illustrations, descriptive examples and personal testimonies from other students bring chapter concepts to life. Empower yourself to make positive changes and improve your health with LIFETIME PHYSICAL FITNESS AND WELLNESS.